2008
DOI: 10.1007/s10549-008-9941-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term “protective” effect of aromatase inhibitors on the endometrium of postmenopausal breast cancer patients

Abstract: Reversal of endometrial thickening induced by long-term tamoxifen treatment in postmenopausal breast cancer patients is maintained throughout long-term aromatase inhibitor treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a meta‐analysis of 5 sequenced therapy trials, the risk of endometrial cancer was substantially lower in women who were sequenced to receive aromatase inhibitors compared with those who continued on tamoxifen (odds ratio, 0.31; P = .007) . In terms of potential mediating mechanisms, a prospective clinical study indicated that long‐term aromatase inhibitor use reversed endometrial thickening associated with tamoxifen …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analysis of 5 sequenced therapy trials, the risk of endometrial cancer was substantially lower in women who were sequenced to receive aromatase inhibitors compared with those who continued on tamoxifen (odds ratio, 0.31; P = .007) . In terms of potential mediating mechanisms, a prospective clinical study indicated that long‐term aromatase inhibitor use reversed endometrial thickening associated with tamoxifen …”
Section: Discussionmentioning
confidence: 99%
“…18 In terms of potential mediating mechanisms, a prospective clinical study indicated that long-term aromatase inhibitor use reversed endometrial thickening associated with tamoxifen. 25 Limited numbers of randomized, placebocontrolled clinical trials have reported the influence of aromatase inhibitors on endometrial cancer in the settings of adjuvant breast cancer 26 and chemoprevention. 13,14 Results from those trials are provided in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Some research supports the association between tamoxifen and endometrial pathology of possible neoplastic potential. Currently, non‐steroidal aromatase inhibitors, which do not stimulate the endometrium and reverse tamoxifen‐induced uterine changes in postmenopausal breast cancer patients, are increasingly being used in the management of breast cancer . Although non‐steroidal aromatase inhibitors are much more expensive, non‐steroidal aromatase inhibitors did not have efficacy in the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, non-steroidal aromatase inhibitors, which do not stimulate the endometrium and reverse tamoxifen-induced uterine changes in postmenopausal breast cancer patients, are increasingly being used in the management of breast cancer. [4][5][6] Although non-steroidal aromatase inhibitors are much more expensive, non-steroidal aromatase inhibitors did not have efficacy in the treatment of breast cancer. Therefore, tamoxifen may still have a role in breast cancer patients diagnosed with estrogen receptor-positive breast cancer because of the different side-effect profiles of new agents.…”
Section: Discussionmentioning
confidence: 99%